Design and performance optimization of a 3D-Printed SIW antenna for free-space applications - Alam, Md Mahabub; Nurhafizah, Abu Talip Yusof; Nurazyyati, Inas; Muhammad Naim, Aminuddin; Bari, Bifta Sama; Yasmin, Abdul Wahab; Mohamad Shaiful, Abdul Karim (University of Diyala, 2025)
his paper presents the design and performance evaluation of a Substrate-Integrated Waveguide (SIW) antenna fabricated using 3D printing technology, with a focus on optimizing its performance for future free-space applications. The proposed antenna integrates an SIW structure with a horn antenna concept, effectively combining the transmitter and receiver functions into a compact, monolithic substrate.This approach provides a miniaturized alternative to conventional free-space material characterization setups, leveraging SIW technology to replace bulky horn antennas with integrated structures. The study demonstrates the feasibility of compact free-space techniques for non-destructive testing, sensing, and electromagnetic material characterization applications.The study involves modeling and simulation using Computer Simulation Technology (CST) software, focusing on antenna performance in the G-band range (4–6 GHz). The fabricated prototype demonstrates resonant frequencies at 5.02 GHz and 6.0 GHz, with a scattering parameter below -10 dB and a well-defined radiation pattern, exhibiting sidelobes at -2.7 dB. The antenna is fabricated using biodegradable Polylactic Acid (PLA) material, reinforcing the potential for sustainable electronics while maintaining structural integrity and electromagnetic compatibility.While this study does not yet validate the antenna for material characterization, the results confirm its feasibility as a compact, cost-effective alternative to conventional free-space setups. This work lays the foundation for further optimization and experimental validation, advancing the role of 3D-printed SIW antennas in free-space applications.